1989
DOI: 10.1002/cm.970140307
|View full text |Cite
|
Sign up to set email alerts
|

Binding of microtubule‐associated proteins (MAPs) to rat brain mitochondria: A comparative study of the binding of MAP2, Its microtubule‐binding and projection domains, and tau proteins

Abstract: Two major brain microtubule-associated proteins (MAPs), MAP2 and tau, were found to be able to bind to purified rat brain mitochondria. The apparent dissociation constants of the binding of thermostable 32P-labeled MAP2 and tau are 0.9 +/- 0.04 x 10(-7) and 3.8 +/- 0.7 x 10(-7) M, respectively. 32P-labeled MAP2 and tau bound to the mitochondria can be displaced by phosphorylated, nonradioactive MAP2. The binding parameters of MAP2 prepared without heat treatment and those of the thermostable MAP2 were of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

1991
1991
1997
1997

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
1
24
1
Order By: Relevance
“…After the incubation time the reaction mixtures were centrifuged at 12,oOOg for 10 min. The radioactivity of bind to mitochondria predominantly via their microtubule binding domain [Jancsik et al, 1989;Rendon et al, 19901 the simplest interpretation is that the location of the interaction site should be situated out of the internal repeats responsible for the binding to tubulin; thus leaving the MAPs free to interact with microtubules to establish a stable bridge between the two organelles. Furthermore, since the C-terminal parts of MAP2 and TAU show sequence homologies, other than the 18 amino acid repeats responsible for the microtubule binding, it is possible to imagine that both MAPs also share a sequence specialized for the interaction with membranous organelles [for a review, see Goedert et al, 19911. In our study we have found that MAP2 exhibits a more pronounced repelling effect than TAU and conversely it is less efficient in establishing the interactions between microtubules and mitochondria.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…After the incubation time the reaction mixtures were centrifuged at 12,oOOg for 10 min. The radioactivity of bind to mitochondria predominantly via their microtubule binding domain [Jancsik et al, 1989;Rendon et al, 19901 the simplest interpretation is that the location of the interaction site should be situated out of the internal repeats responsible for the binding to tubulin; thus leaving the MAPs free to interact with microtubules to establish a stable bridge between the two organelles. Furthermore, since the C-terminal parts of MAP2 and TAU show sequence homologies, other than the 18 amino acid repeats responsible for the microtubule binding, it is possible to imagine that both MAPs also share a sequence specialized for the interaction with membranous organelles [for a review, see Goedert et al, 19911. In our study we have found that MAP2 exhibits a more pronounced repelling effect than TAU and conversely it is less efficient in establishing the interactions between microtubules and mitochondria.…”
Section: Discussionmentioning
confidence: 98%
“…We observed that 32P-labeled MAP2 and TAU bound to mitochondria could be displaced by phosphorylated unlabeled MAP2. We also provided evidence that MAP2 and TAU bound to mitochondria predominantly via their microtubule-binding domain [Jancsik et al, 1989;Rendon et al, 19901. To better understand at the molecular level the mitochondria-microtubule interaction we studied here whether microtubules could bind to rat brain mitochondria in an acellular system. The use of '251-labeled tubulin [Carlier et al, 19801, that keeps its ability to assemble into microtubules has permitted the quantification of the mitochondria-microtubule interaction.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…These mitochondria may be transported along microtubules perhaps bound to MAP-2. Studies have shown that MAP-2 binds to mitochondria via the microtubulebinding domain (Jancsik et al, 1989). In addition, MAP-2 isolated from rat brain preparations binds to the outer membrane of mitochondria (Linden et al, …”
Section: Discussionmentioning
confidence: 99%
“…This has confirmed the involvement of MAPs in this type of association (Blocker et al 1996;Schrader et al 1996) while eliminating motors that bind to microtubules in a nucleotide-dependent fashion. Studies of this sort have shown neuronal MAP2 and tau to be capable of anchoring organelles to microtubules (Linden et al 1989;Jancsik et al 1989;Jung et al 1993). Other nonneuronal MAPs, some of which have been designated cytoplasmic linker proteins or CLIPs (Rickard and Kreis 1996), have also been implicated.…”
Section: Introductionmentioning
confidence: 96%